Taxpayers' Perceptions of Practitioners: Finding One Who is Effective and Does the Right Thing? - Sakurai, Yuka (Journal of business ethics, 2003)
This paper examines Australian taxpayers' perceptions of their idealized tax practitioner as well as their perceptions of their current tax preparer. The analysis was based on survey responses from 2,040 randomly selected Australian taxpayers who completed the "Community Hopes, Fears and Actions Survey" (author, 2000). Three dimensions were identified as underlying taxpayer judgements of their idealized practitioner. A minority of the sample indicated that their ideal was a creative, aggressive tax planning type, a person who was well networked and familiar with tax office intelligence and enforcement priorities. A second type of idealized practitioner engaged in the cautious minimisation of tax. Unlike creative accountants, practitioners of this type avoided conflict, while being sophisticated about identifying opportunities to minimise tax. The most popular idealized type was the low risk, no fuss practitioner who was honest and risk averse. The data revealed that taxpayers are likely to find tax practitioners who have the attributes that they value most highly, but that when taxpayers' perceptions of their tax practitioner are combined with their ideals, only two substantive dimensions emerge, tax avoidance and doing the right thing. Our inability to distinguish tax practitioners who are seen to provide cautious and aggressive advice in practice has important implications for the growth of aggressive tax planning markets in the community.